Lesson Learned on the District Health System Operation from the Project to Solve the Problem of Motorcycle Accidents and Death among Children and Youth in Klongtom District, Krabi Province, Thailand - Khunnikom, Prawit; Benjatanawat, Suvapak (Al-HIKMAH Journal, 2024)
This qualitative research in the form of a case study aimed to learn the lessons on the district health system operation from the project to solve the problem of motorcycle accidents and death among children and youth based on the UCCARE concept. Data were collected by reviewing related documents, two focus group discussions, and a brainstorming meeting between October and September 2022. Fifty key informants comprising fifteen district health committees, two chief administrators of the subdistrict administrative organization, three public health officers, seven directors of health-promoting hospitals/community health centers, one hospital officer responsible for accidental work, five professional nurses, seven sub-district patrolmen, two traffic police, three teachers, and five village health volunteers. Data were accurately checked by triangulation and then analyzed by content and descriptive analysis. The result revealed that the district health operational lessons can be explained based on the UCCARE concept in 6 components, namely 1) Unity team: setting directional goals, making a joint commitment, and having the mechanism for monitoring and evaluation obviously; 2) Customer focus: giving importance to children and youth who were the target group both the leaders with roles and abilities and the general children and youth in schools and communities; 3) Community participation and network: both formal and informal participation; 4) Appreciation: appreciating and valuing to organizations and individuals driving the management of traffic accidents; 5) Resource sharing and human development of district health committees: Sharing of resources, both tangible resources such as budgets and intangible resources such as knowledge and expertise of the individual; and 6) Essential care: solving the problem of motorcycle accidents and death/improving the quality of life of people according to the area context by considering the economy ability, and available of motorcycles for children and youth for using, apart from the expressing of individual behavior.